Energy evolution and key parameters of coal breaking by flexible cutting tools - Yong LIU; Zhikang ZHANG; Jianping WEI; Xiangyu XU; Yingjun GAO (Meitan xuebao)
To solve the difficulties such as the small range of unloading pressure in hard coal seams and poor permeability enhancement effect, based on the water dynamic flexible cutting coal unloading and permeability enhancement technology, the combination of the quality and impact velocity of the terminal end teeth was optimized when the kinetic energy of the terminal end teeth was constant, in order to improve energy utilization and coal breaking efficiency. Therefore, flexible cutting coal impact experiments were carried out, and the coal fragmentation quality and average fragmentation depth under different conditions of terminal end teeth quality and velocity were analyzed. A numerical simulation method of particle flow was used to establish a model of flexible cutting coal impact with the terminal end teeth, and the energy of the coal body and the evolution law of the cracks during the coal breaking process were analyzed to reveal the influence mechanism of the terminal end teeth quality and impact velocity on the effect of flexible cutting coal impact. Results show that when the kinetic energy of the end teeth is constant, with a decrease in tooth mass and an increase in impact velocity, the quality of coal fragmentation and the average depth of fragmentation both show an initial increase followed by a decrease in trend. The area of coal shear crushing zone, total number of cracks, and the distance from the deepest axial main crack to the surface of the coal body all show an initial increase followed by a decrease in trend. After the end teeth come into contact with the coal body, the kinetic energy of the teeth rapidly decreases, principally transforming into the coal’s strain energy and frictional energy. The accumulation and release of strain energy leads to the generation of a large number of cracks directly below the teeth, forming a semi-circular shear crushing zone. Around the shear crushing zone, there is a concentration of stress at the weakly bonded areas of the cracks, resulting in the formation of main cracks that extend outward. When the kinetic energy of the end teeth is 60.3 J, with a tooth impact velocity of 38.8 m/s and a mass of 0.08 kg, the coal fragmentation effect is optimal. As the impact velocity of the end teeth increases, the energy density acting on the coal body increases per unit time, but the impact force decreases, causing the peak strain energy of the coal body to first increase and then decrease. When the peak strain energy is at its maximum, the coal body exhibits the best crushing effect.